Impact of sample storage conditions on gliclazide quantification in rat plasma by UHPLC/UV method: storage recommendation and pharmacokinetic application - Nesrin F. Taha, Ebtesam W. Elsayed, Ahmed A. El-Ashmawy, Aya R. Abdou, Laila H. Emara (Journal of Applied Pharmaceutical Science, 2021)
The effect of different storage durations/temperatures on the stability of gliclazide (GLZ) in plasma was not studied before in the literature. A simple, reproducible ultra-high performance liquid chromatography coupled with ultraviolet detection (UHPLC/UV) was established for monitoring GLZ in rat plasma was established, with all stability parameters fully evaluated. The developed method provided simple solvent extraction for both GLZ and Glibenclamide as an internal standard (I.S.) with a short run time (≤ 7 minutes). A linear calibration curve (0.1–40 µg/ml), with good intra- and inter-day precision and accuracy, was established based on 40-ul plasma volume. Lower and upper limits of quantification allowed effective monitoring of the expected variations in GLZ absorption. The stock solution, freeze–thaw, short-term and bench stability results safeguard the rationale of the UHPLC/UV method. However, GLZ plasma samples were only stable for 1 week storage at −20°C or −80°C. The present study emphasized the importance of proper storage conditions, with recommendations for direct analysis of GLZ in plasma after sample collection or maximum storage for 1 week at −20°C or −80°C until analysis, to ensure accurate measurement of the drug in plasma. This method was effectively applied in a pharmacokinetic study of GLZ single oral dose from the market product Diamicron® MR 30 mg administered in six rats.
Keywords: Long-term plasma stability, gliclazide, validation, UHPLC/UV, pharmacokinetics.